Effective therapeutic targeting of tumor lineage plasticity in neuroendocrine prostate cancer by BRD4 inhibitors - Xiong Zhang; Yatian Yang; Hongye Zou; Yang Yang; Xingling Zheng; Eva Corey; Amina Zoubeidi; Nicolas Mitsiades; Ai-Ming Yu; Yuanpei Li; Hong-Wu Chen (Acta Pharmaceutica Sinica B)
Tumor lineage plasticity (LP) is an emerging hallmark of cancer progression. Through pharmacologically probing the function of epigenetic regulators in prostate cancer cells and organoids, we identified bromodomain protein BRD4 as a crucial player. Integrated ChIP-seq and RNA-seq analysis of tumors revealed, for the first time, that BRD4 directly activates hundreds of genes in the LP programs which include neurogenesis, axonogenesis, EMT and stem cells and key drivers such as POU3F2 (BRN2), ASCL1/2, NeuroD1, SOX2/9, RUNX1/2 and DLL3. Interestingly, BRD4 genome occupancy is reprogrammed by anti-AR drugs from facilitating AR function in CRPC cells to activating the LP programs and is facilitated by pioneer factor FOXA1. Significantly, we demonstrated that BRD4 inhibitor AZD5153, currently at clinical development, possesses potent activities in complete blockade of tumor growth of both de novo neuroendocrine prostate cancer (NEPC) and treatment-induced NEPC PDXs and that suppression of tumor expression of LP programs through reduction of local chromatin accessibility is the primary mechanism of action (MOA) by AZD5153. Together, our study revealed that BRD4 plays a fundamental role in direct activation of tumor LP programs and that its inhibitor AZD5153 is highly promising in effective treatment of the lethal forms of the diseases.